The Disequilibrium Approach to Monopolistic Price Setting and General Monopolistic Equilibrium - Benassy, Jean-Pascal (Review of Economic Studies, 1976)
Journal Article The Disequilibrium Approach to Monopolistic Price Setting and General Monopolistic Equilibrium Get access Jean-Pascal Benassy Jean-Pascal Benassy CEPREMAP Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 1, February 1976, Pages 69–81, https://doi.org/10.2307/2296601 Published: 01 February 1976 Article history Received: 01 July 1974 Accepted: 01 March 1975 Published: 01 February 1976